Derivation and Validation of a Nomogram for Predicting 90-Day Survival in Patients With HBV-Related Acute-on-Chronic Liver Failure - Chen, Jun-feng; Weng, Wei-zhen; Huang, Miao; Peng, Xiao-hua; He, Jian-rong; Zhang, Jing; Xiong, Jing; Zhang, Shao-quan; Cao, Hui-juan; Gao, Bin; Lin, Deng-na; Gao, Juan; et al. (Frontiers in Medicine, 2021)
Background & Aims: Conventional prognostic models do not fully reflect the severity of hepatitis B virus (HBV)-related acute-on-chronic liver failure (ACLF). This study aimed to establish an effective and convenient nomogram for patients with HBV-related ACLF. Methods: A nomogram was developed based on a retrospective cohort of 1,353 patients treated at the Third Affiliated Hospital of Sun Yat-sen University from January 2010 to June 2016. The predictive accuracy and discriminatory ability of the nomogram were determined by a concordance index (C-index) and calibration curve, and were compared with current scoring systems. The results were validated using an independent retrospective cohort of 669 patients consecutively treated at the same institution from July 2016 to March 2018. This study is registered at ClinicalTrials.gov (NCT03992898). Results: Multivariable analysis of the derivation cohort found that independent predictors of 90-day survival were age, white blood cell count, hemoglobin, aspartate aminotransferase, total bilirubin, international normalized ratio, serum creatinine, alpha fetoprotein, serum sodium, hepatic encephalopathy, pre-existing chronic liver disease, and HBV DNA load. All factors were included in the nomogram. The nomogram calibration curve for the probability of 90-day survival indicated that nomogram-based predictions were in good agreement with actual observations. The C-index of the nomogram was 0.790, which was statistically significantly greater than those for the current scoring systems in the derivation cohort (P<0.001). The results were confirmed in the validation cohort. Conclusions: The proposed nomogram is more accurate in predicting the 90-day survival of patients with HBV-related ACLF than current commonly used methods.